1976
DOI: 10.1901/jaba.1976.9-127
|View full text |Cite
|
Sign up to set email alerts
|

THE SOCIAL VALIDATION AND TRAINING OF CONVERSATIONAL SKILLS1

Abstract: Three reliably measured components of conversation-questioning, providing positive feedback, and proportion of time spent talking-were identified and validated as to their social importance. The social validity of the three conversational behaviors was established with five female university students and five female junior-high students. Each was videotaped in conversations with previously unknown adults. The conversational ability of each girl was evaluated by a group of 13 adult judges who viewed each tape a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(78 citation statements)
references
References 10 publications
2
75
0
1
Order By: Relevance
“…Unfortunately, normative measures of conversational skills are rarely assessed. In a notable exception, Minkin et al (1976) asked naïve judges to rate conversation samples of female college and junior high school students during unstructured conversations, and the judges rated the college students more favorably. The authors found that the college students engaged in more questioning and positive feedback than the junior high school students, suggesting that these two behaviors are important conversational skills.…”
mentioning
confidence: 99%
“…Unfortunately, normative measures of conversational skills are rarely assessed. In a notable exception, Minkin et al (1976) asked naïve judges to rate conversation samples of female college and junior high school students during unstructured conversations, and the judges rated the college students more favorably. The authors found that the college students engaged in more questioning and positive feedback than the junior high school students, suggesting that these two behaviors are important conversational skills.…”
mentioning
confidence: 99%
“…In a more recent review of program evaluations of delinquency treatment, Elliott (1980) . The treatment approach is based on behavioral principles and the premise that deviant behavior might be reduced or prevented by providing youths with relationships with adults who have high reinforcing value, who provide differential consequences for youth behavior, and who teach requisite social, academic, and self-care skills for successful community living (Braukmann, Kirigin, & Wolf, 1980 (Phillips, 1968); the self-government system ; the teaching procedures used to develop the youths' social, academic, and self-care behaviors (Maloney, Harper, Braukmann, Fixsen, Phillips, & Wolf, 1976;Minkin, Braukmann, Minkin, Timbers, Fixsen, Phillips, & Wolf, 1976;Werner, Minkin, Minkin, Fixsen, Phillips, & Wolf, 1975); the home-based report card system (Bailey, Wolf, & Phillips, 1970;Kirigin, Phillips, Timbers, Fixsen, & Wolf, 1977); and vocational training procedures (Braukmann, Maloney, Fixsen, Phillips, & Wolf, 1974 (Braukmann, Fixsen, Kirigin, Phillips, Phillips, & Wolf, 1975). The year long, in-service training sequence consists of two 1-wk workshops, frequent telephone and periodic inhome consultation session, and regular formal evaluations (Braukmann,Kirigin,& Wolf,Note 1).…”
mentioning
confidence: 99%
“…Contingent upon the targeting of a spe- consistently evaluated all participants' posttraining performance more favorably than their pretraining performance. Because these managers were naive as to which tapes were before or after training, their evaluations provide "social validation" of the overall training outcome (Minkin, Braukman, Minkin, Timbers, Timbers, Fixsen, Phillips, & Wolf, 1976 Historically, education and training programs for mentally retarded adolescents and adults have focused a great deal of attention on the acquisition of specific vocational skills, often in special workshop settings. However, in order to actually become economically and personally independent, potentially employable retarded persons will need to convey their employability to prospective employers.…”
Section: Discussionmentioning
confidence: 99%